Pembelajaran Smash Permainan Bola Voli : Ujicoba Skala Kecil - Destriana Destriana; Destriani Destriani; Herri Yusfi (Jurnal MensSana, 2021)
The purpose of this study was to test the volleyball drills smash learning technique. It is hoped that this experiment can produce a product that can be used for learning volleyball smash games. The method in this research is R&D at the stage of small-scale field trials with quantitative and qualitative data analysis techniques. The instruments used in this study were observation and questionnaires. This study involved 3 observers and 24 physical education students as research respondents. This research found that 88.9% of students can do the drills smash learning technique and this is also supported by the results of observations made by 3 observers, it was found that an average of 89.4% of students could apply the volleyball learning drills smash technique. This shows that the volleyball drills smash learning technique on small-scale trials can be used and applied to students.